La comprensión lectora: una variable significativa de la calidad educativa - Aliaga Murray, Nelly (2010)
This article focuses on the releVance of comprehensive reading throughout the history of education, and on which has been the trend in our country. This paper describes, from a psycholinguistic and pedagogical approach, how reading comprehension is understood nowadays focusing on how the text intervenes in the allocation of meaning and the importanceof metacognitive processes, as well as the memory functions in the cognitive process of the reading comprehension.